Clinical Cases in Geriatric Exfoliative Dermatitis - Lotti, Torello M.; Wollina, Uwe.; Olisova, Olga.; Jafferany, Mohammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual cases using best practice techniques and this title focuses on the management of exfoliative dermatitis, also known as "red man". This is an important discipline in older patients as the recognition and appropriate management of these conditions requires the clinician to distinguish often very subtle differences in the presentation of patients. This practical case-based reference helps readers accurately define the diagnostic and management criteria to assist clinical decision-making. Clinical Cases in Geriatric Exfoliative Dermatitis highlights evidence-based best practice in managing erythroderma in older patients. It uses a thorough multidisciplinary case-based approach that is relevant to the scenarios that dermatologists face in clinical practice, while also providing insights for pharmacologists and pathologists that work with these cases.
Drug eruption -- Dermatitis -- Atopic dermatitis -- Psoriasis -- Pityriasis rubra pilaris -- Contact dermatitis -- Stasis dermatitis (venous eczema) -- Seborrhoeic dermatitis -- Blistering diseases -- Sezary syndrome -- Congenital ichthyotic conditions -- Lymphoma and leukaemia -- Carcinoma of rectum, lung, fallopian tubes, colon, prostate -- Graft-versus-host disease -- HIV infection.
Keywords: Dermatology; Geriatrics; Dermatology; Geriatrics; Dermatitis